2022
DOI: 10.3389/fonc.2022.973109
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F-FDG PET/CT in patients affected by pulmonary primary lymphoma

Abstract: BackgroundPrimary pulmonary lymphoma (PPL) is defined as clonal abnormal hyperplasia of lung parenchyma or bronchial lymphoid tissue originating from bronchial mucosal tissue. However, PPL is rare, which accounts for approximately 3-4% of extraneurotic lymphomas and 0.5-1% of all primary tumors in the lung. Owing to the lack of any typical clinical symptoms and radiological features, it is challenging to accurately diagnose PPL, which affects its clinical management and prognosis. Considering this, herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It is difficult to distinguish NUT from other pulmonary tumors based solely on PET/CT findings. Previous literature reported that the SUV max of pulmonary squamous cell carcinoma ranged from 3.1 to 30.2 ( 6 ), the SUV max of lung adenocarcinoma ranged from 2.2 to 18.1 ( 53 ), the SUV max of pulmonary primary lymphoma ranged from 2.58 to 22.6 ( 54 ), the SUV max of small cell lung cancer ranged from 3.3 to 29.9 ( 55 ). And there is no obvious difference compared with the data for lung NUT we summarized above.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to distinguish NUT from other pulmonary tumors based solely on PET/CT findings. Previous literature reported that the SUV max of pulmonary squamous cell carcinoma ranged from 3.1 to 30.2 ( 6 ), the SUV max of lung adenocarcinoma ranged from 2.2 to 18.1 ( 53 ), the SUV max of pulmonary primary lymphoma ranged from 2.58 to 22.6 ( 54 ), the SUV max of small cell lung cancer ranged from 3.3 to 29.9 ( 55 ). And there is no obvious difference compared with the data for lung NUT we summarized above.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other studies, a defining feature of MALT was the absence of significant mediastinal or hilar adenopathy. In the opinion of most researchers, MALT is essentially extranodal lymphomas according to the diagnostic criteria, rarely involving hilar and mediastinal lymph nodes ( 29 ). In addition, pleural invasion, as indicated by pleural effusion was less frequent in C-MALT than P-LADC.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the extensive genomic sequencing approaches, both mutation-related and pathologically variable molecular features of lung cancers have been elaborated. In fact, an accumulation of such datasets has also helped to successfully and effectively define (diagnostically) diverse lung cancer types ranging from non-small cell lung cancer (NSCLC: squamous cell carcinoma and non-squamous cell carcinoma) to small cell lung cancer (SCLC: limited stage SCLC and extensive stage SCLC) [ 1 , 2 , 3 , 4 ]. However, it is still unclear how lung cancer cells can escape the immune system, posing a serious challenge to treatment resistance.…”
Section: Introductionmentioning
confidence: 99%